Hand Functions Following Prone-weight Bearing on Upper Limb with Active Elbow Extension Versus Modified Constraint Induced Movement Therapy in Children with Unilateral Cerebral Palsy - A Randomised Clinical Trial - Narayan, Amitesh; Bavighar, Ruth; Krishnan, Shyam; Alammari, Abdulaziz; Karnad, Shreekanth D; Poojari, Deepalaxmi Paresh (NeuroRehabilitation (Reading, Mass.), 2025)
Background The atypical upper limb (UL) flexion pattern in children with unilateral cerebral palsy (UCP) debilitates their ability to experience natural weight bearing through arms and hands, leading to restricted mobility and reduced hand functions. The recommended therapeutic strategies to improve hand functions are not standardized, i.e., (varied protocols, treatment schedules, and frequency), though the benefits of UL weight-bearing on hand-opening and prehension skills are well-documented. Objective To study the efficacy of Static weight bearing (SWB) in Prone on UL with active elbow extension versus modified-constrained induced movement therapy (m-CIMT) on hand functions in children with UCP. Methods Randomized clinical trial. Subjects (N = 38) were randomized equally (group- 1, SWB, n = 19; and group- 2, m-CIMT, n = 19). Outcome measure- Fine Motor of PDMS-2 (FM_PDMS-2) pre-and post-interventions after 2 weeks. Results The percentage change (post-intervention) for the Grasping and VMI subtests in the SWB group were 37.67% and 14.11%, while for the m-CIMT group were 12.78% and 4.88%, respectively. These changes were highly significant (p 0.000). Conclusion Both groups, i.e., SWB and m-CIMT, showed significant differences in the percentage change post-intervention. However, the SWB group demonstrated augmented changes over the m-CIMT on both subtests of FM_PDMS-2, hence greater improvement in hand functions following SWB exercises.